التطبيب الذاتي لاستخدام المضادات الحيوية بين مرتادي الصيدليات الخاصة في ساحل-محافظة حضرموت-اليمن: Banafa, Nawal Said al-Kuthayri, Muna Umar - Banafa, Nawal Said al-Kuthayri, Muna Umar (مجلة الأندلس للعلوم التطبيقية, 2023)
الملخص EN Background : Self-medication might certainly albeit gradually lead to self-killing in the worst cases. According to the world health organization,the Self-medication is defined as “selection and use of medicines by individuals (or a member of the individuals’ family) to treat self-recognized or selfdiagnosed conditions or symptoms”(1). The main problem with selfmedication with antibiotics is the emergence of pathogenic resistance, which is an existing problem worldwide .Some studiesin the USA have also revealed considerable self-medication with antibiotics obtained from leftovers previous courses, at a local pharmacy or outside the country (2). The problem of self-medication is widely spread in developing countries; Yemen is one of this country .In Yemen the quality of healthcare services isn’t in a good condition, and it needs great efforts to be developed the private sector’s pharmacies are the most accessible health facilities and people can obtain most types of medication without prescription making the selfmedication easy to be practiced. A previous study was conducted in Yemen about the antibiotics selfmedication among the children and showed highly alarming percentage representing 60 % 1, 2. In Our study we will explore the prevalence of self-medication of antibiotics use without medical prescription among private pharmacies visitors in Coast Hadhramout governate –Yemen Objective : To assess the self-medication of antibiotics use among private pharmacies visitors in Coast Hadhramout governate–Yemen. Subject and Methods: A cross sectional descriptive study was conducted on private pharmacies in different areas of Coast Hadhramout governate was carried out from October to December 2015 which was using self-administered questionnaire among 300 private pharmacies visitors selected randomly. Results : This study shows that the prevalence of self-medication of antibiotics use without medical prescription is highly percentage 85%, which amoxicillin is the most used self-prescribed antibiotic and previous prescription use (74 %) is the most common self-medication of antibiotics information source. Difficulty of accessing health services is the main reason for the self-medication among private pharmacies visitors in Coast Hadhramout governate. Conclusion : The present study indicate that self-medication of antibiotics practice has been common among private pharmacies visitors in our local community, so we recommend to the ministry of health to do more efforts to make close observation for private pharmacies to prevent giving medications without prescription.